Associations of overall sitting time and TV viewing time with fibrinogen and C reactive protein: the AusDiab study. Issue 4 (18th February 2014) - Howard, Bethany J; Balkau, Beverley; Thorp, Alicia A; Magliano, Dianna J; Shaw, Jonathan E; Owen, Neville; Dunstan, David W
Abstract : Background/aim: Sedentary behaviour is associated with increased risk for all-cause and cardiovascular mortality. Plasma fibrinogen and C reactive protein (CRP)—key inflammatory and/or haemostatic markers—may contribute to this association; however, few studies have examined their relationships with sedentary behaviours. We examined associations of overall sitting and TV viewing time with fibrinogen and high-sensitivity CRP (hsCRP). Methods: Plasma fibrinogen and hsCRP were measured in 3086 Australian adults (mean age: 55±12 years) who participated in the 2004–2005 AusDiab (Australian Diabetes, Obesity and Lifestyle) study. Multiple linear regression analyses examined cross-sectional associations of self-reported overall sitting and TV viewing time (h/day) with plasma fibrinogen and hsCRP, adjusting for sociodemographic, behavioural and medical treatments and conditions as potential covariates. Results: Overall sitting time and TV viewing time were positively associated with plasma fibrinogen (sitting: β: 0.02 g/L, 95% CI (0.01 to 0.02); TV time: 0.03 g/L (0.02 to 0.05)) and hsCRP (sitting: 2.4% (1.2% to 3.6%); TV time: 4.5% (1.7% to 7.4%)). Associations were independent of leisure-time physical activity, but after adjusting for waist circumference, they remained for fibrinogen, but for hsCRP were attenuated to the null. Interactions were observed for gender×TV (p=0.011) with fibrinogen (associations in women only) and for waist circumference×TV (p=0.084) with hsCRP (associations in low-risk only). Conclusions: Overall sitting time was positively associated with plasma fibrinogen and hsCRP in men and women; associations of TV viewing time with fibrinogen were observed in women only. Abdominal adiposity-mediated associations for hsCRP but not for fibrinogen. Prospective and intervention studies are needed to establish likely causality and elucidate potential mechanisms.